Data assessment of cardiovascular system remodeling in patients prior and after kidney transplantation - S. M. Martirosyan; E. D. Kosmacheva (Инновационная медицина Кубани, 2019)
Object of assessment is patients following kidney transplantation.Objective. We defined the grade of myocardial remodeling in patients after transplantation during the 1-year period.Materials and Methods. We analyzed 125 patients prior to transplantation, in 6 months and in 1 year postoperatively. The comparative assessment of cardiovascular system remodeling indicators was carried out. Conclusion. In the analyzed population, frequency and myocardial hypertrophy of the left ventricle evidence showed tendency to decrease after kidney transplantation that was defined by targeted levels of arterial pressure achievement and improved indicators of the glomerular filtration.